Penerapan Pembelajaran Flipped Classroom terhadap Hasil Belajar Matematika Siswa Kelas X SMKN 1 Sapuran - Eka Rahma Tirani; Heru Kurniawan; Wharyanti Ika Purwaningsih (Universitas Muhammadiyah Purworejo, 2022)
This study aims to determine whether the mathematics learning outcomes of students subjected to the flipped classroom are better than those of students subjected to conventional learning models. The type of research used is quasi-experimental research. The sample of this research is 34 students of class X TKRO 1 and 33 students of class X AKL 3 SMKN 1 Sapuran. The sampling technique used was random sampling. The data collection technique used is the documentation method and the test method. The analytical technique used is data analysis with a balance test and data analysis after treatment with a t-test hypothesis. The results of the calculation of the hypothesis test in the experimental class and control class are tcount = 2,976 and the value of ttable = 1,669 with DK = so that H0 rejected. Based on the test decision stating H0 was rejected, then this study concludes that the learning outcomes subjected to the flipped classroom are better than the learning outcomes subjected to the conventional learning model.